2020
DOI: 10.1097/psy.0000000000000873
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Out-of-Class Mindfulness Practice Adherence During and After a Mindfulness-Based Intervention

Abstract: Objective: Out-of-class mindfulness meditation practice is a health behavior that is considered to be a crucial ingredient in mindfulness-based interventions (MBIs), yet participant adherence to practice recommendations is often inconsistent. Furthermore, MBIs may enhance factors that lead to greater adherence to medical regimens in other contexts. This study examined baseline factors previously found to relate to adherence to medical regimen, MBI-related changes in these baseline factors, and treatment-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Participants in both groups listened to the audios during MS more than post-MS. We think that the differences in duration and number of audio listening between groups, and between MS and post-MS might be explained by some unexplored factors. A 2021 study by Canby, NK et al [51] showed that baseline conscientiousness, openness, and depressive symptoms predicted intervention meditation adherence. Hence, we think that our participants' personality traits may have been different at the baseline and this affected adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in both groups listened to the audios during MS more than post-MS. We think that the differences in duration and number of audio listening between groups, and between MS and post-MS might be explained by some unexplored factors. A 2021 study by Canby, NK et al [51] showed that baseline conscientiousness, openness, and depressive symptoms predicted intervention meditation adherence. Hence, we think that our participants' personality traits may have been different at the baseline and this affected adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the depression level of Group B was alleviated to some degree by the PSA before the beginning of MS, and this may have led to lower adherence to audio listening in Group B. The Canby, NK et al study [51] also reported conscientiousness and depressive symptoms predicted post-intervention adherence. We think that the lower number of audio listening after MS than during MS in both groups might be because their depression had already improved.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in both groups listened to the audios during MS more than post-MS. We think that the differences in duration and number of audio listening sessions between groups, and between MS and post-MS, might be explained by some unexplored factors. A 2021 study by Canby et al [ 51 ] showed that baseline conscientiousness, openness, and depressive symptoms predicted intervention meditation adherence. Hence, we think that our participants’ personality traits may have been different at the baseline and that this affected adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the depression level of Group B was alleviated to some degree by the PSA before the beginning of MS, which may have led to lower adherence to audio listening sessions in Group B. The Canby et al, study [ 51 ] also reported that conscientiousness and depressive symptoms predicted post-intervention adherence. We think that the lower number of audio listening sessions after MS than during MS in both groups might be because their depression had already improved.…”
Section: Discussionmentioning
confidence: 99%
“…So far, personality traits as predictors of mindfulness outcomes had been less considered. Findings from recent studies seem to suggest that trait consciousness is related to meditation and program adherence (Canby et al, 2021 ; Cillessen et al, 2020 ). However, this is the first time that the relation between personality traits as measured by the PiCD and treatment outcomes of MBCT is explored.…”
Section: Discussionmentioning
confidence: 99%